Mineral dust observed with AERONET Sun photometer, Raman lidar, and in situ instruments during SAMUM 2006 : Shape-dependent particle properties - Mueller, D.; Ansmann, A.; Freudenthaler, V.; Kandler, K.; Toledano, C.; Hiebsch, A.; Gasteiger, J.; Esselborn, M.; Tesche, Matthias; Heese, B.; Althausen, D.; Weinzierl, B.; et al. (Journal of Geophysical Research, 2010)
Nearly pure Saharan dust was observed with an Aerosol Robotic Network (AERONET) Sun photometer, several Raman and high spectral resolution lidars, and airborne in situ instruments during the Saharan Mineral Dust Experiment (SAMUM) 2006 in Morocco. In the framework of a case study we present particle shape-dependent dust properties, i.e., backscatter coefficients, extinction-to-backscatter (lidar) ratios, and linear particle depolarization ratios. These parameters can be inferred from AERONET's latest version of the mineral dust retrieval algorithm. The parameters can be measured with multiwavelength Raman/depolarization lidar without critical assumptions on particle shape. Lidar ratios inferred from the AERONET Sun photometer data tend to be larger than lidar ratios measured directly with lidar. Linear dust depolarization ratios were derived for several measurement wavelengths from the data products of the AERONET Sun photometer. The depolarization ratios tend to be smaller than the depolarization ratios measured with lidar. The largest differences exist in the near-ultraviolet wavelength range. Particle axis ratios were determined with scanning electron microscopy. The axis ratio distribution differs significantly from the axis ratio distribution that is assumed in the AERONET retrievals. If the axis ratio distributions measured during SAMUM are used, the reproducibility of the lidar data products improves. The differences may in part be caused by an insufficient understanding of the light-scattering model that is used in the AERONET algorithm. The results of the present study will be used to develop a dust light-scattering model that will serve as the theoretical basis for the inversion of optical data into dust microphysical properties. Peer reviewed